UMP Orator Club organises International Online Pidato Malaysia Sejahtera 2020 - Juwairiah, Osman (2021)
KUANTAN, 19 December 2020 - The Universiti Malaysia Pahang (UMP) Orator Club has successfully organised the International Online Pidato Malaysia Sejahtera 2020, attended by 116 participants from within and outside the country.